Intensity of thermal convection in beehives - Gakashev, Arsen Ildarovich; Tarunin, Evgeniy Leonidovich (Computational Continuum Mechanics, 2008)
The necessity of considering thermal convection in beehives is motivated by its influence on the survival of bees during winter months. Convection taking place in beehives develops in a complex fashion because of their complicated geometry and is accompanied by many phenomena, which cannot be taken properly into account. In this paper, calculations of thermal convection in beehives are carried out with consideration of the inter-frames inner convection current circulation for different geometric parameters.